High consciousness—low application: sustainable development and sustainable healthcare in undergraduate physiotherapy education in Sweden - Swärdh, Emma; Brodin, Nina; Palstam, Annie; Pettersson, Anna (Frontiers in Public Health, 2024)
BackgroundSwedish undergraduate physiotherapy education lacks comprehensive integration of sustainable development in curricula. Factors related to educators’ perspectives in preparing future physiotherapists for sustainable development and sustainable healthcare may shed light on this shortcoming.AimThis study aims to describe Swedish physiotherapy educators’ (i) consciousness of sustainable development and its inclusion in teaching and learning activities, (ii) ecological worldviews, (iii) attitudes toward sustainability and climate change in physiotherapy, (iv) perceptions of education for sustainable development and sustainable healthcare and (v) examine the relationship between ecological worldview and attitudes toward sustainability and climate change in physiotherapy.MethodA cross-sectional, descriptive study was performed using a digital survey to collect data from educators within undergraduate physiotherapy education at five higher education institutions in Sweden. Data was collected using the Sustainability Consciousness Questionnaire, the New Ecological Paradigm Scale, the Sustainability Attitudes in Nursing Survey 2, and questions related to knowledge, attitudes, and self-efficacy for education for sustainable development and sustainable healthcare.ResultMost, but not all, of the 72 educators, (76%) were aware of Agenda 2030 and the sustainable development goals, and 17% included perspectives related to sustainable development in teaching and learning activities. The educators endorsed an eco-centered ecological worldview and had largely positive overall attitudes toward sustainability and climate change within physiotherapy. However, almost one-third (28%) disagreed that issues about climate change should be included in the physiotherapy curriculum. Most agreed about having content knowledge on climate and health (81%), while a smaller part agreed on having pedagogical content knowledge regarding how to inspire or educate for sustainable development (17–28%). There was also a wide variation in perceived self-efficacy in education for sustainable development and sustainable healthcare.ConclusionDespite the endorsement of eco-centered ecological worldviews and a rather high consciousness of sustainable development as an overall concept, there remains a disconnect to educational attitudes and actions among Swedish physiotherapy educators. This points to the need to explore the narrative of sustainable development within physiotherapy in Sweden rooted in broader concept understanding, ethics, and reflective practice for sustainable development. A key priority should be to offer new perspectives on professional identity and continuing professional development within sustainable development.